Morphological and phylogenetic evidence reveal Fissuroma taiwanense sp. Nov. (Aigialaceae, Pleosporales) from Hedychium coronarium - Danushka S. Tennakoon (2018)
© 2018 Magnolia Press. Fissuroma taiwanense sp. nov. was collected from Shihnong Forest Area in Chiayi, Taiwan (Elevation 350m) and is the first report of a Fissuroma species from Hedychium (Zingiberaceae). The species is markedly different from extant species of Fissuroma in having broad cylindric-clavate asci with long, club-shaped apical and basal appendages and distinct thick mucilaginous sheath in ascospores. Combined analyses of LSU, SSU and tef1-α sequence data indicate a close relationship with F. maculans, the type species, but isolates of the new taxon are phylogenetically distinct. The new species is compared with other Fissuroma species and a comprehensive description and micrographs are provided.